Pengembangan Petunjuk Praktikum Fisika Dasar I Berbasis 5M Untuk Melatih Keterampilan Proses Sains dan Karakter Wasaka - Misbah, Misbah; Wati, Mustika; prastika, miranti diah (Jurnal Fisika FLUX, 2018)
ABSTRACTâ The manual for practicum that has been used for the teaching and learning activities has not been maximal in training the science process skills and student character in conducting an investigation. Therefore, research and development on the basic physics lab manual I based on 5M to train the science and character process skills of Wasaka was conducted. The purpose of this study is to describe the feasibility of 5M Basic Physics practice manual for training the science process skills and Wasaka character in terms of the validity aspects. This research is a research and development using a modified 4D model. The instrument used in this study was in the form of validation sheets of the basic Physics I Basic Physics manual 5 M. Based on the results of data analysis obtained that the instructions of practicum basic physics I based on 5 M train the science process skills and the characters of Wasaka categorized as very valid.